Green T Energy : Micro Hydro Electric Turbine / Mohamad Irfan Mohamad Sukeri...[et al.] - Mohamad Sukeri, Mohamad Irfan; Selamat, Mohamad Noor Risyam; Ngah, Aiman Faris; Mustapha, Muhammad Asyraf; Mohd Jamal, Nurul Hawa Basirah (2016)
Our objective is to promote a greener, cleaner and more environmentally friendly way of generating energy. We hope to expand our business nationwide, by having at least a branch in every state. By doing this the price can be more reasonable, and we are able to promote our product to a wider range of customers. By doing this, we are able to see an increase in our total revenue. Our product's strength is that it is a very eco-friendly and affordable way to produce energy. It is also reasonably prices as well as portable. However, it is still in its early stage, therefore may not be as efficient as the other product of this nature. Most of the camping essentials provider do not sell any type of generator as it is too big and not portable. By having this indirect competitor, the micro-hydro-electric generator would be a wanted item among campers, hikers and outdoor activists nationwide. The micro-hydro-electric generator is made for a sole purpose of using water in order to generate electricity while being light and portable. The key feature of this product are its portability, reasonably prices, little-to-no harmful emissions and low operating cost